2021
DOI: 10.3389/fcimb.2021.777709
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Host-Leptospira Interactions: What We Know and Future Expectations

Abstract: Leptospirosis is a widespread zoonosis caused by pathogenic Leptospira spp. It is considered a neglected infectious disease of human and veterinary concern. Our group has been investigating proteins annotated as hypothetical, predicted to be located on the leptospiral surface. Because of their location, these proteins may have the ability to interact with various host components, which could allow establishment of the infection. These proteins act as adherence factors by binding to host receptor molecules, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 135 publications
(238 reference statements)
2
20
0
Order By: Relevance
“…Although many studies have shown that leptospires are able to bind to mammalian cells in vitro [ 4 ], this is the first study to investigate leptospires binding to mammalian cells using multiple different cell lines. We determined the adhesion profile of virulent, culture-attenuated and saprophytic strains of leptospires in EA.hy926, HMEC-1 and HULEC5a endothelial cells, in HEK293T and MDBK epithelial cells, and in E. Derm and BHK-21 fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies have shown that leptospires are able to bind to mammalian cells in vitro [ 4 ], this is the first study to investigate leptospires binding to mammalian cells using multiple different cell lines. We determined the adhesion profile of virulent, culture-attenuated and saprophytic strains of leptospires in EA.hy926, HMEC-1 and HULEC5a endothelial cells, in HEK293T and MDBK epithelial cells, and in E. Derm and BHK-21 fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we investigated if the virulent, attenuated, and saprophytic strains of Leptospira and their major outer membrane proteins could bind to different mammalian cells, including endothelial and epithelial cells and fibroblasts. The first studies of leptospires adhesion to mammalian cells showed that virulent strains are more effective in binding to cells than are attenuated and saprophytic bacteria [ 4 ]. It was demonstrated that strains of L. interrogans serovars Canicola, Pomona, and Grippothyphosa interact with MDCK and PK-15 epithelial cells and HUVEC endothelial cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of leptospirosis depends on the combination of the host species and the Leptospira serovars, but the link between the host-pathogen pairing and the outcome is ambiguous. Though it would be the consequence of a complicated host-pathogen interaction, such as an immunological attack and evasion [46], which might lead us to understand the mechanism from the Leptospira dynamics on the host tissues. The adhesivity and crawling-dependent spread investigated on kidney cells of various mammalian hosts show a positive correlation, and the typical maintenance host rat shows a lower score against pathogenic strains (i.e., low adhesivity and limited spread) [38].…”
Section: Host Preferencementioning
confidence: 99%
“…[ 13 , 14 ]. Besides these cell wall and cell membrane components, many virulence factors from the pathogenic Leptospira were identified and the structures and functions of this virulence were well studied in several reviews [ 15 , 16 , 17 ]. In addition, nucleotide-binding oligomerization domain-containing protein 1 and 2 (NOD1 and NOD2) in the innate immune system are also very important pattern recognition receptors.…”
Section: Introductionmentioning
confidence: 99%